Two-step adsorption kinetics of malachite green on anionic polystyrene microspheres in aqueous solution probed by second harmonic generation. Issue 32 (8th August 2017) - Kim, Joon Heon
Abstract : Adsorption of organic cations of malachite green on anionic microspheres was monitored in real time using a surface-specific second-harmonic generation technique, and its two-step characteristic was investigated. Abstract : Adsorption of organic cations of malachite green (MG) on an anionic microsphere surface was monitored in real time using a surface-specific second-harmonic generation (SHG) technique. This adsorption was found to consist of two processes of different timescales for all MG concentrations, which has not been considered in previous SHG experiments. The two-step adsorption can be well explained by our suggested model, which consists of an initial fast electrostatic alignment of weakly bound MG followed by slow non-electrostatic adsorption of MG on the surface of a microsphere. This study shows the importance of kinetics measurements in providing full understanding of adsorption of charged molecules on colloid surfaces.